2017
DOI: 10.1242/jeb.157792
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb muscle function in turtles: is novel skeletal design correlated with novel muscle function?

Abstract: Variations in musculoskeletal lever systems have formed an important foundation for predictions about the diversity of muscle function and organismal performance. Changes in the structure of lever systems may be coupled with changes in muscle use and give rise to novel muscle functions. The two extant turtle lineages, cryptodires and pleurodires, exhibit differences in hindlimb structure. Cryptodires possess the ancestral musculoskeletal morphology, with most hip muscles originating on the pelvic girdle, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Comparative studies of keel function in animals have produced varied results: while some have found that keels improve stability and hydrodynamic performance [4, 22,23,34], others have failed to find that keels decrease body oscillations [52]. Such differences in the results across studies might arise from other features of body shape that were not controlled for in our comparisons, such as subtle differences in keel shape between our structures and those found in nature, as well as possible differences in the lateral margins of the turtle carapace that are associated with keels, or the kinematic patterns that freshwater turtles use relative to fishes [53][54][55]. In addition, whereas our study focused on how intrinsic perturbations arising from limb movements during linear swimming impacted performance, it is possible that keels may, instead, have a greater effect on stability when animals are recovering from extrinsic perturbations.…”
Section: Keel Function In Turtles Compared With Engineered Vehiclesmentioning
confidence: 88%
“…Comparative studies of keel function in animals have produced varied results: while some have found that keels improve stability and hydrodynamic performance [4, 22,23,34], others have failed to find that keels decrease body oscillations [52]. Such differences in the results across studies might arise from other features of body shape that were not controlled for in our comparisons, such as subtle differences in keel shape between our structures and those found in nature, as well as possible differences in the lateral margins of the turtle carapace that are associated with keels, or the kinematic patterns that freshwater turtles use relative to fishes [53][54][55]. In addition, whereas our study focused on how intrinsic perturbations arising from limb movements during linear swimming impacted performance, it is possible that keels may, instead, have a greater effect on stability when animals are recovering from extrinsic perturbations.…”
Section: Keel Function In Turtles Compared With Engineered Vehiclesmentioning
confidence: 88%
“…EMG motor patterns for terrestrial forward locomotion (walking) share some features with EMG motor patterns for the three forms of scratch and the two forms of swimming, including rhythmic alternation between hip-flexor and hip-extensor activities (Earhart and Stein 2000b;Mayerl et al 2017). The timing of the monoarticular knee extensor during walking is particularly interesting in that it fires in two distinct bursts during the step cycle, once during hip flexion and a second time during hip extension.…”
Section: Focal Electrical Stimulation Of the Turtle Spinal Cord Can Evoke Swimming Behaviorsmentioning
confidence: 99%
“…Turtle hindlimb musculature has been well described (Mayerl et al 2017;Walker 1973). Muscles that have received special attention in studies (Bakker and Crowe 1982;Robertson et al 1985;Stein and Daniels-McQueen 2003) are 1) the hip flexor, also called hip protractor, VP-HP, puboischiofemoralis internus, pars anteroventralis; 2) the hip extensor, also called hip retractor, HR-KF, flexor cruris, pars flexor tibialis internus; 3) the monoarticular knee extensor, FT-KE, triceps femoris, pars femorotibialis; 4) the biarticular knee extensor and hip adductor, AM-KE, triceps femoris, pars ambiens; 5) the biarticular knee extensor, hip abductor, and hip flexor, IT-KE, triceps femoris, pars iliotibialis; and 6) the knee flexor, ILFIB, iliofibularis.…”
Section: Hindlimb Motor Neurons and Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to soft tissue anatomy, muscle activation patterns can only be measured in living animals through electromyography (EMG), which provides insights into the timing, intensity, and frequency of myoelectric signals across a range of speed and locomotor modes employed by an animal (Blob et al., 2008; Cappellini et al., 2006; Foster & Higham, 2014; Gatesy, 1994, 1997; Gorvet et al., 2020; Loeb & Gans, 1986; Mayerl et al., 2017; Rivera & Blob, 2010; von Tscharner, 2000; Wakeling et al., 2002). With regard to shifts in posture, a comparison of hindlimb muscle activation in American alligators showed increases in the activation of knee and ankle extensors when assuming a more upright limb posture (Reilly & Blob, 2003).…”
Section: Introductionmentioning
confidence: 99%